Digestive caecum and tissue redistribution in gill of Telescopium telescopium as indicators of Ni bioavailabilities and contamination in the tropical intertidal area - Yap, Chee Kong; Arifin, Noorhaidah; Tan, Soon Guan (Springer Netherlands, 2012)
The relationships between the Ni concentrations of the mudflat snails Telescopium telescopium and the surface sediments have not been reported yet from tropical intertidal areas. In this study, telescope snails and surface sediments were collected from 18 geographical sampling sites in intertidal areas of Peninsular Malaysia. The concentrations of Ni were measured in seven different soft tissues of the snails namely foot, cephalic tentacles, mantle, muscle, gill, digestive cecum, and remaining soft tissues. It was found that different concentrations of Ni were found in the different soft tissues, indicating different mechanisms of sequestration and regulation of Ni in these different tissues. By comparing the Ni concentrations in the similar tissues, spatial variations of Ni were found in the different sampling sites although there was no consistent pattern of Ni in these sites. The highest Ni variation based on the ratio of maximum to minimum values indicated that cephalic tentacle and foot were the main organs having high Ni variation. The use of correlation analysis and multiple linear stepwise regression analysis revealed that digestive cecum of T. telescopium could be used to reflect the Ni contamination of the sampling site. Also, the digestive cecum and gill were found to be the main bioaccumulation and storage sites for Ni. From the Ni accumulation patterns in all the populations investigated, tissue redistributions of Ni in gill was identified and could be proposed as an indicator of high Ni bioavailability and contamination in the sampling site. To our knowledge, this is the first and most comprehensive study on Ni accumulation in the different soft tissues of T. telescopium from tropical intertidal areas, in relation to the sediment data.